KONSELING INDIVIDUAL PESERTA DIDIK BERKESULITAN BELAJAR DAN PENGENTASAN MELALUI STRATEGI PEKERJAAN RUMAH DAN FONIK - Elpiani Rambe; Bukhari Is (Tarbiyah bil Qalam : Jurnal Pendidikan Agama dan Sains, 2020)
This study aims to reveal a number of learning difficulties for grade 3 of studentsat Sekolah Dasar Negeri (SDN) Balirejo Yogyakarta. They have difficulty learningbased on symptoms that appear when learning. This research type is a field researchusing a qualitative research to the type of case study. The results revealed that the typesof learning difficulties of students (based on information from homeroom teachersand subject teachers) were lazy to learn, slow in understanding questions, slow inwriting and reading. After the researchers conduct counseling, provide exercises inthe form of text and based on the theory the researcher reads, the learning difficultiesof students include the slow learner types and selections. The results of individualcounseling indicate that there are changes and progress in student learning. Bycarrying out individual counseling and alleviation solutions through homework andphonics strategies, students/counselees more easily understand each question, morediligently coming to school, better understanding how to read correctly and writeneatly and correctly. The counseling phase conducted by researchers starts from theplanning, implementation, evaluation, follow-up stages and reports on counselingresults.